Artificial Intelligence in Pharma Industry - A Review - Shah, Niyati (Asian Journal of Pharmaceutics (AJP), 2023)
The use of artificial intelligence (AI) in pharmaceutical technology has grown over time, and it may help save time and money while also improving our understanding of the connections between various formulations and process parameters. AI is a subfield of computer science called intelligence that focuses on the use of symbolic programming to solve problems. It has significantly developed into a problem-solving science with numerous applications in business, medicine, and engineering. The article discusses the development of novel peptides from natural foods, the treatment and management of rare diseases, drug adherence and dosage, and challenges to the adoption of AI in pharma. It also discusses manufacturing execution systems, automated control process systems, and AI to predict new treatments. Key words: ACPS, challenges to adoption